Perioperative and Short-Term Outcomes of Sinus Replacement and Conservative Repair for Aortic Root in Acute Type A Aortic Dissection: A Prospective Cohort Study - Chang, Yi; Qian, Xiangyang; Guo, Hongwei; Wei, Yizhen; Yu, Cuntao; Sun, Xiaogang; Wei, Bo; Ma, Qiong; Shi, Yi (Frontiers in Cardiovascular Medicine, 2022)
Background To compare outcomes between sinus replacement (SR) and conservative repair (CR) for dissected roots with normal size. Methods From October 2018 to April 2021, a prospective cohort study was carried out. Patients were assigned to two groups (SR group and CR group) according to whether they underwent sinus replacement. Propensity score matching was applied to adjust preoperative variables and Kaplan–Meier method was used for survival analysis. Results Three hundred and eighty-seven patients were enrolled. In the whole cohort, 18 patients (4.7%) died postoperatively. The operative mortality of SR group was comparable to CR group (3.2% vs. 6.0%, p = 0.192 before matching; 3.5% vs. 7.0%, p = 0.267 after matching) and the incidence of hemostasis management under restarted cardiopulmonary bypass for root bleeding was lower in SR group (1.6% vs. 7.0%, p = 0.002 before matching; 2.1% vs. 8.5%, p = 0.03 after matching). The median follow-up duration was 12 months. There were 3 reoperations in the CR group. The estimated cumulative event rate of reoperation was 1.1 % at 12 months and 1.6% at 24 months in CR group, with a trend of a lower rate in the SR group (log-rank p = 0.089 before matching, p = 0.075 after matching). There was one late death in each group. The estimated cumulative event rate of death was 3.8% at 12 months and 24 months in the SR group, and was 6.6% in the CR group with no significant difference (log-rank p = 0.218 before matching, p = 0.120 after matching). Aortic regurgitation significantly improved postoperatively and remained stable during follow-up. Conclusions Sinus replacement is a simple, safe, and effective technique for repairing severely dissected sinus with a comparable time spent in operation and excellent immediate and short-term results. It had the advantages of eliminating false lumen and avoiding aortic root bleeding.